Clearance of apoptotic cells by macrophage in MCF-7 cell line treated with methanol extract of centella asiatica (MECA) - Muhamad, Nor ‘Atiqah (2018)
Breast cancer is one of the major contributions in non-communicable diseases worldwide. To date, much evidence has shown that resistance to apoptosis by cancer cells and inefficient efferocytosis by phagocytic cells in cancer patients foster the development of other diseases in cancer patients, such as autoimmune diseases. Previous studies have shown that Centella asiatica (C. asiatica) extract induced apoptosis in cancer cell line but there was a lack of study regarding efferocytosis against cancer cells. C. asiatica has the potential to be an alternative treatment to induce apoptosis and efferocytosis by phagocytic cells in cancer patients. The anti-proliferative activity of methanol extract of C. asiatica (MECA) against breast cancer cell line (MCF-7) was obtained by performing methylene blue assay (MBA). In this method, DMSO served as a negative control while tamoxifen served as a positive control. After that, the mode of cell death in MECA-treated cells was determined by Hoechst 33342 staining and was further investigated by flow cytometry analysis. The findings on the MBA suggested that MECA was cytotoxic on MCF-7 and not toxic on normal cells (NIH3T3). Furthermore, MCF-7 treated with MECA undergone increased apoptosis indicated by brighter fluorescence, alteration of nuclear morphology and DNA fragmentation observed in Hoechst staining. To study efferocytosis activity by macrophages (J774A.1), MCF-7 cells were cultivated in J774A.1 cells with multiplicity of infection (MOI) of 1:2. After treatment with MECA, flow cytometry data showed a significant increase of late apoptotic cells due to apoptosis of J774A.1 after engulfing MCF-7 cells. In conclusion, MECA was able to improve the activities of apoptosis and efferocytosis in MCF-7 cells, thus suggesting a promising alternative treatment for breast cancer.